Overview of assessment of enterprise assets according to national accounting standards in the context of safe risks - Zatoka, Tetiana (Technology audit and production reserves, 2022)
The prerequisites for revising the revaluation of non-current assets of an enterprise and highlighting the methodological aspects of applying individual national accounting standards (regulations) are considered. The object of the study is the assessment of the assets of the enterprise, which is necessary for the reliable display of information about assets in the financial statements, in the presence of security risks. The application of a valuation requires professional judgment to be made about the fair value of the subject matter. At the same time, the concept of fair, market, net realizable value must be divided taking into account the requirements of national accounting standards (regulations) (NAS(R)). In the case that national standards do not provide an answer to certain questions of the methodology for establishing and revising estimates, the norms of international financial reporting standards should be taken into account. Recognition of accounting items at fair value today is widely used in international practice, in contrast to the Ukrainian experience. Valuation and accounting are interrelated concepts, since financial statements must reflect complete, reliable and impartial information about the value of accounting objects. Today, in Ukrainian accounting, the issue of carrying out the recognition procedure at fair value remains important. This is due to the lack of specific methodological support for this procedure. An analysis of the existing requirements for determining the fair value of certain types of assets makes it possible to make decisions on the basic approach to valuation of assets in the presence of security risks. It was determined that the signs of depreciation of assets under martial law with a high degree of probability is a decrease in the market value of the asset during the reporting period significantly more than expected. This group of signs also includes physical damage to the asset; significant negative changes in the external environment; Significant changes in the way the asset is used during the reporting period.